Comparison of Socio Economic Development of Tarai and Nepal - Duvey, Dipak (Research Nepal Journal of Development Studies, 2020)
The comparison of socio economic development of Tarai and Nepal is the comparison of development of total Nepal with its southern part Tarai. Socio economically southern belt of Nepal, Tarai is leading whole Nepal in development. There are not any significant impacts of conflicts of Tarai in one and half decade, in socio economic development of rural development of Tarai. The comparative study has selected timeline of 2004, 2011 and 2019 to collect and analyze the socioeconomic indicators based on data of Central Bureau of Statistics (CBS Data). It is the study of literacy rate, access to electricity, GDP Growth rate and Per capita income of Nepal and Tarai region in different point of time of conflicts and resiliencies. The literacy rate was 55%, 65%, and72% in Tarai and 49%, 60% and 69% in Nepal; access to electricity were 40%, 78% and 95% in Tarai and 37%, 65% and 96% in Nepal. Similarly, Gross Domestic Product (GDP) Growth rate was 5%, 5% and 7.2% in Tarai and 4.7 %, 3.4%, and 7.1% in Nepal; Per capita income in USD was 300, 629 and 1100 in Tarai and 286, 610, and 1034 in Nepal from 2004, 2011, and 2019respectively. Therefore, Tarai is leading Nepal in socio economic development.